Reflexion in mathematical models of decision-making. Issue 3 (4th May 2018) - Novikov, Dmitry; Korepanov, Vsevolod; Chkhartishvili, Alexander
Abstract: The paper is devoted to a generalization of static and dynamic mathematical models of behavior with explicitly stated reflexive models of agents' decision-making. Reflexion is considered as agent's beliefs about nature, opponents' beliefs and opponents' decision-making principles in the framework of game theory, collective behavior theory and learning models. Abstract :